Optimising antiemesis in cancer chemotherapy: efficacy of continuous versus intermittent infusion of high dose metoclopramide in emesis induced by cisplatin. Issue 6558 (22nd November 1986) - Warrington, P S; Allan, S G; Cornbleet, M A; MacPherson, J S; Smyth, J F; Leonard, R C
Abstract : Thirty three untreated patients being given cisplatin received metoclopramide (7 mg/kg) for antiemesis by either continuous or intermittent infusion in a random order. Each patient received intravenous dexamethasone in addition. High pressure liquid chromatography was used to measure plasma concentrations of metoclopramide. The two regimens were evaluated for antiemetic efficacy and the incidence of side effects. The intermittent metoclopramide regimen resulted in peak and trough plasma concentrations of metoclopramide with accumulation at eight hours, while the loading dose and continuous infusion resulted in mean plasma concentrations greater than 0.85 micrograms/ml (2.8 mumol/l) throughout the eight hour period. The continuous infusion was associated with a significant improvement in nausea and vomiting and reduction in diarrhoea. Major control of emesis (two episodes or fewer) was achieved in 27 patients receiving continuous metoclopramide compared with 18 receiving intermittent metoclopramide.